Using CT imaging to identify sarcopenia as a risk factor for severe falls in older adults - Nadja Fries; Angeliki Kotti; Mischa Woisetschläger; Anna Spångeus (BMC Geriatrics)
Abstract Background Sarcopenia is a skeletal muscle disease primarily associated with ageing and progressive muscle decline and increases the risk of falls. The purpose of the present study was to investigate risk factors, including sarcopenia, for severe falls compared to non-severe falls. In addition, we wanted to explore possible associations between sarcopenia, bone mineral density (BMD), adipose tissue as well as clinical scores assessing frailty, nutritional status, and fall risk. Methods This retrospective cohort study included 101 older patients that had experienced a fall incident during in-patient care at a geriatric ward between 2018 and 2020. The fall incidents were categorized into severe or non-severe falls. Clinical data, including risk assessment scores were retrospectively obtained from the participants’ medical records. Body composition, including skeletal muscle quantity (SKM), adipose tissues, and BMD were assessed from abdominal CT-scans performed for any reason maximal 6 months before or after the fall. Skeletal muscle index ratio (SMI-ratio) was calculated using SKM cm2/height m2 and divided with previous described cut off values for sarcopenia. An SMI ratio < 100% indicated sarcopenia. Results The severe fall group showed higher grade of sarcopenia compared to the non-severe fall group (SMI ratio of 71% vs. 83%, p = 0.041) as well as lower, though statistically non-significant, BMI and subcutaneous adipose tissue (SAT) (BMI 22 [20–24] vs. 24 [22–27] kg/m2, p = 0.108, and SAT 95 ± 70 cm² vs. 141 ± 94 cm², p = 0.124). Overweight was more common in non-severe than severe fall group (43% vs. 14%, p = 0.048). SMI ratio correlated negatively with frailty and positive with BMI and the following body composition measurements: intramuscular-, subcutaneous, and visceral adipose tissue (IMAT, SAT and VAT). No correlation with other clinical risk assessment scores nor spine T-score was found. In the multivariate analysis, higher level of frailty, male sex as well as lower BMI, VAT and SAT remained as risk factors for low SMI ratio. Conclusions These results underscore the importance of addressing sarcopenia and related risk factors, including malnutrition, in the management and prevention of severe falls in the elderly population. Body composition analyzed in CT-scans could add value in this risk assessment. This analysis could be conducted opportunistically during CT scans performed for other purposes.